Diagnostic Utility of Qualitative MRI and T2 Relaxometry in Hippocampal Assessment for Temporal Lobe Epilepsy - Sajida Majeed, Farooque Ahmed Haidari, Fareed Khan, Aimal Khan, Binish Zaidi, Farzeen Arshad (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To determine the diagnostic value of qualitative MRI and T2 relaxometry in hippocampal assessment for temporal lobe epilepsy. Study Settings: Department of Radiology, Sheikh Zayed Hospital, Rahimyarkhan. Duration of Study: January to June 2023 Data Collection: A cross-sectional, single-center study was conducted involving 110 EEG-confirmed seizure patients. All participants underwent MRI with a dedicated epilepsy protocol including T2 relaxometry. Hippocampal T2 relaxation times were calculated by placing Regions of Interest (ROIs) on each slice of the hippocampus. Results: A total of 110 TLE patients were studied; 65.5% were aged 10–40 years and 58.2% were male. T2 relaxometry detected hippocampal sclerosis in 34.5%, while visual MRI identified 41.8%. Diagnostic accuracy showed 31.8% true positives, 55.5% true negatives, 2.7% false negatives, and 10.0% false positives. Conclusion: T2 relaxometry showed strong agreement with visual MRI in identifying hippocampal sclerosis. It serves as a reliable adjunct tool for enhancing diagnostic accuracy in temporal lobe epilepsy. Keywords: Temporal Lobe Epilepsy, Mesial Temporal Sclerosis, T2 Relaxometry, MRI, EEG, Hippocampus